CIRCULAR SUSTAINABILITY IN UNIVERSITY SYSTEM : THE IDENTIFICATION - Juli Nurdiana (Jurnal Teknologi Lingkungan UNMUL, 2017)
Abstract           Although sustainability is now becoming main issue in any areas including for education, in regards to putting closed-loop thinking at the heart of education system, it is revealed that Indonesia is still lagging behind. This study presents a descriptive analysis aimed to identify the important remarks of sustainability and circular economy based on the literature review, to help Indonesian universities in setting their  future direction towards sustainability and circularity.Keywords: circular economy, sustainability, Indonesian  university